2020
DOI: 10.1021/acs.chemmater.9b04614
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Disorder Tolerance in Piezoelectric Materials and Design of Polar Systems

Abstract: Current high-performing piezoelectric materials are dominated by perovskites that rely on soft optical phonon modes stabilized by disorder near a morphotropic phase boundary and a unique resilience of the polar response to that disorder. To identify structural families with similar resilience, we develop a firstprinciples sensitivity analysis approach to determine the effect of disorder on the piezoelectric response for structures in the Materials Project database. In well-known piezoelectric systems, the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…The optoelectronic properties of the synthesizable polymorphs in this system remain to be investigated, and Table I indicates promising properties for device applications such as contact materials, solar cell absorbers, photocatalysts, piezoelectric and ferroelectric materials. [16,44] In particular, the synthesized BN-derived polymorph has >2 eV band gap and low (<1.5) well-matched electron and hole effective masses, making it interesting for electronic devices that can operate at elevated temperatures. Additionally, this non-polar BN polymorph is the transition state between two variants of the polar WZ structure, suggesting a pathway to tuning its predicted and measured ferroelectric response.…”
Section: Discussionmentioning
confidence: 99%
“…The optoelectronic properties of the synthesizable polymorphs in this system remain to be investigated, and Table I indicates promising properties for device applications such as contact materials, solar cell absorbers, photocatalysts, piezoelectric and ferroelectric materials. [16,44] In particular, the synthesized BN-derived polymorph has >2 eV band gap and low (<1.5) well-matched electron and hole effective masses, making it interesting for electronic devices that can operate at elevated temperatures. Additionally, this non-polar BN polymorph is the transition state between two variants of the polar WZ structure, suggesting a pathway to tuning its predicted and measured ferroelectric response.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the dielectric and piezoelectric tensors are often correlated due to the inclusion of the Born effective charges and force constants. , We neglect the contribution of the electronic term in the piezoelectric calculation, e̅ , in this study as it generally does not contribute significantly to the total piezoelectric tensor for the materials currently computed in the Materials Project database . Once the piezoelectric properties for the fully substituted alloys are computed, we approximate the piezoelectric tensor for the intermediate compositions of the substitutional alloy systems by employing a Vegard’s-law-like linear approximation for the Born effective charges, internal stain tensors, and force constants of the alloy.…”
Section: Methodsmentioning
confidence: 99%
“…Following the recommendations obtained by DFT calculations for enhanced polar behavior, the system is synthesized through pulsed-laser deposition and increased dielectric properties are found. Along with this general methodology for systematically exploring disorder-tolerant piezoelectric alloy systems, we identify Sr 2 Nb 2–2 x V 2 x O 7 as a promising system with confirmed increased dielectric and predicted increased piezoelectric properties.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent ab initio predictions have shown that even apart from a prospective structural‐phase boundary, Pb 1− x Sr x HfO 3 could exhibit enhanced piezoresponse as a function of ionic disorder (associated with the strontium alloying). [ 28 ] Finally, strontium alloying is well known to improve the leakage and breakdown strength of lead‐based perovskites [ 29 ] and thus there is potential that the Pb 1− x Sr x HfO 3 system could provide a pathway to improved capacitive energy storage performance. The key parameters underlying capacitive‐energy storage of any dielectric material are the recoverable energy density in the charge–discharge process (normalUnormalr=PmaxPrEdP , where P r and P max are the remanent and maximum polarization, respectively) and the energy‐storage loss ( U loss , which is determined by the area enclosed within the double hysteresis loops).…”
Section: Introductionmentioning
confidence: 99%